2003
DOI: 10.1074/jbc.m308213200
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Roles of Fyn and Cortactin in Cell Migration of Metastatic Murine Melanoma

Abstract: Src family kinases are major regulators of various integrin-mediated biological processes, although their functional roles and substrates in cancer metastasis are unknown. We explored the roles of Src family tyrosine kinases in cell migration and the spread of K-1735 murine melanoma cell lines with low or high metastatic potential. Corresponding to elevated cell motility and spreading ability, Fyn was selectively activated among Src family kinases, and the cell motility was blocked by an inhibitor of Src famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 34 publications
4
57
0
Order By: Relevance
“…Marchetti et al used brain metastatic sublines and found that kinase activity of Yes, not c-Src, was elevated compared to low-metastatic cells. We recently reported that, in a metastatic model of murine melanoma cell lines, kinase activity of Fyn was elevated in high-metastatic sublines, and interacted with cortactin (Huang et al, 2003). Although not as significant as in the case of murine melanoma, Fyn will also be a candidate for the responsible kinase for metastatic potential of human osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Marchetti et al used brain metastatic sublines and found that kinase activity of Yes, not c-Src, was elevated compared to low-metastatic cells. We recently reported that, in a metastatic model of murine melanoma cell lines, kinase activity of Fyn was elevated in high-metastatic sublines, and interacted with cortactin (Huang et al, 2003). Although not as significant as in the case of murine melanoma, Fyn will also be a candidate for the responsible kinase for metastatic potential of human osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Cdc28 is the main CDK driving the cell cycle in budding yeast. Genetic interactions with checkpoint and APC mutants suggest Cdc28 may regulate checkpoint arrest downstream of the Budesonide-treated tumors also show decreased expression of the proto-oncogene Fyn, which is associated with tumor progression in cancer models including oral squamous cell carcinoma and metastatic murine melanoma (Huang et al, 2003;Li et al, 2003). This suggests a progressive phenotype for the It was recently reported that a combination treatment of dexamethasone and cisplatin on solid tumors of the lung and cervix resulted in less apoptosis compared with cisplatin alone (Herr et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Interplay between Src kinases and cortactin seems to be important particularly in cells of high metastatic potential (Li et al, 2001;Huang et al, 2003). Hence, activation of the cortactin-WIP-Arp2/3 pathway is likely an additional mechanism by which activated Src augments cell motility in a tumor.…”
Section: Role Of Cortactinmentioning
confidence: 99%